Relationship between full-thickness macular hole and retinal break/lattice degeneration - ZhangJinglin; LiYonghao; ZhaoXiujuan; CaiYu; YuXiling; LuLin (眼科学报, 2015)
Background: The purpose is to investigate the relationship between full-thickness macular hole (MH) and retinal break (RB) and/or lattice degeneration. Methods: Patients diagnosed as full-thickness MH and referred to Dr. Lin Lu from January 2009 to December 2013 were evaluated. All patients underwent general ophthalmologic examinations, fundus examination and optical coherence tomography (OCT). The RB and/or lattice degeneration were recorded. Results: Totally 183 eyes of 167 patients were included. The sex ratio of men to women was 1:2.88. A total of 17 eyes were pseudophakic and 166 eyes were phakic. RB and/or lattice degeneration were found in 62 eyes (33.88%). The prevalence of RB and/or lattice degeneration was similar between men and women (P=0.344>0.05). There was no statistical difference between the pseudophakic eyes and phakic eyes (P=0.138>0.05). All of the RB and/or lattice degeneration were located near or anterior to the equator. The inferior quadrants and the vertical meridian were affected more often than the superior quadrants and the horizontal meridian. Conclusions: We identified a high incidence of RB/lattice degeneration in cases of full-thickness MH. Carefully examination of the peripheral retina and prophylactic treatment of RB and/or lattice degeneration are critical.